Mortgage-related Financial Difficulties: Evidence from Australian Micro-level Data - La Cava, Gianni; Read, Matthew; Stewart, Chris (Sydney, 2014)
We investigate the factors associated with the incidence of mortgage-related financial difficulties in Australia. We use two complementary micro-level datasets: loan-level data on residential mortgages from two Australian banks, which we use to analyse the factors associated with entering 90+ day housing loan arrears; and household-level data from the Household, Income and Labour Dynamics in Australia (HILDA) Survey, which we use to explore the factors associated with households missing mortgage payments. The loan-level analysis indicates that the probability of entering arrears increases with the loan-to-valuation ratio (LVR) at origination, and is particularly high for loans with an LVR above 90 per cent. In contrast, the probability of entering arrears is lower for loans that are repaid relatively quickly. Additionally, the probability of entering arrears varies across different loan types; for example, low-documentation loans are more likely to enter arrears, even after controlling for whether the borrower was self-employed. The likelihood of entering arrears increases with the contract interest rate, which is consistent with lenders setting higher interest rates for riskier borrowers. The household-level analysis suggests that the probability of missing a mortgage payment is particularly high for households with relatively high debt-servicing ratios. Households that have previously missed a payment are also much more likely to miss subsequent payments than households with unblemished payment histories.
Research Discussion Paper No 2014-13
Research Discussion Papers
Keywords: Stress -- Financial stress; Housing; Income & Finance -- Mortgage; Income, wealth and finances; Housing; Income & Finance; Stress; Financial stress; Mortgage; Income, wealth and finances